PRINSIP PEMANFAATAN SUMBER DAYA ALAM BERBASIS BIOSENTRIS DALAM PERSPEKTIF ISLAM - Heru Kurniawan; Mukhamad Hamid Samiaji (Research Institute and Community Engagement of IAIN MADURA, 2017)
The biocentric basis in the utilization of natural resources is rooted in the realization that nature is the center of life that must be respected. Through nature all life behavior patterns are formed. To that end, the human’s behaviors in treating and utilizing natural resources should be based on: (1) the principle of respect for nature, (2) the principle of responsibility, (3) the principle of solidarity, and (4) the principle of compassion and care for nature. Principles which in the Islamic conception are implemented through the attitude of utilizing natural resources as well as possible, are able to explore secrets in natural resources well, and take care of natural resources. With this exploitation, nature is positioned in a biocentric reality, that is, as the center of life that must be respected with high moral and religious awareness.